Pengaruh Keterlibatan Karyawan, Lingkungan Kerja Dan Budaya Organisasi Terhadap Kinerja Karyawan (Studi Pada UMKM Pelaku Usaha Madu Di Kota Malang) - Febian Aqila Adaby; Afi Rachmat Slamet; Sulton Sholehuddin (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study analyzes the influence of employee engagement, work environment, and organizational culture on employee performance in honey-based MSMEs in Malang City. This research is motivated by the importance of optimizing human resources as a key factor in organizational performance, especially in MSMEs that still face challenges such as low employee involvement, less supportive work environments, and suboptimal organizational culture. The study aims to examine both simultaneous and partial effects of these variables on employee performance. A quantitative explanatory approach was employed using a saturated sampling technique involving 49 employees. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that simultaneously all variables significantly affect employee performance. Partially, employee engagement has a positive and significant effect, while work environment and organizational culture do not show significant effects. These findings suggest that employee engagement is the most dominant factor in improving employee performance. Therefore, MSMEs should prioritize strategies that enhance employee engagement to improve performance outcomes. Keyword : Employee engagement, Work environment, Organizational culture, Employee performance